The Obscure Meaning of M. Quraish Shihab's Perspective in Tafsir Al-Misbah - Abdul Muiz; Musthofa (Tilawah: Journal of Al-Qur'an Studies, 2025)
One of the aspects of the human mind which is the focus point of the Qur'an is mental health from the disease of arrogant nature and arrogant behavior that has long occurred since the first human existence of Prophet Adam as the devil was envious of the creation of Prophet Adam as. Scholars themselves differ on the meaning of takabur. This study aims to analyze the interpretation of the interpretation of Al-Mishbah by M.Quraish Shihab on the verse that discusses takabur, as well as find out the relevance of what is happening in the current era. This research provides new directions or insights for the reader and most importantly distances or minimizes society not to be arrogant because the impact is very large for oneself and for others. This research approach is a qualitative research with the type of library research (library research). The type of research is description analysis. The meaning of Takabur according to M.Quraish Shihab in his interpretation of A-Mishbah is pride in seeing oneself as better than others. Many people do not realize or feel that what they are doing is arrogance and arrogance, they enjoy what they have too much and forget where they got what they have.